PENGARUH METODE DRILL TERHADAP KEMAMPUAN SERVIS BAWAH PEMBELAJARAN BOLA VOLI PADA KELAS VIII SMPN 1 KLARI - Sifa Fauziah; Sutirna; Suherman, Asep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this study is to find out the influence of drill methods on the under-service capabilities in the SMPN 1 Klari volleyball game. The approach used in this study is a quantitative approach with experimental research methods using true experimental design in the form of pretest-posttest control group design. The population in this study is the whole of the students of the eighth grade SMPN 1 Klari out of 436. The total sample in this study was 62 people from 31 experimental classes and 31 control classes. The results showed that by comparing the results of the pretest-posttest the experimental class showed the average value of 55,290 with the standard deviation of 5,786. Whereas the result of the Pretest-Posttest of the control class shows that the mean value of 21,484 with the default deviation is 3,829. As for the result of the t test using sig (2-tailed) that is 0,000 < 0.05 then Ho was rejected and Hi accepted so that the results of the treatment that the researchers did there was a significant difference, this suggests there was an influence on the drill method on the service ability under the volleyball game.